Auricularia polytricha and Flammulina velutipes ameliorate inflammation and modulate the gut microbiota via regulation of NF-κB and Keap1/Nrf2 signaling pathways on DSS-induced inflammatory bowel disease. (June 2022) - Nguepi Tsopmejio, Ivan Stève; Ding, Miao; Wei, Jiali; Zhao, Cong; Jiang, Yu; Li, Yuting; Song, Hui
Abstract: Flammulina velutipes and Auricularia polytricha are two popular dietary mushrooms, especially in the Northeast of China. They have revealed many pharmacological effects due to their bioactive compounds, but their possible mechanism of action involved in inflammation remains poorly known. Therefore, Inflammatory bowel disease (IBD) which is a chronic disease and progressive inflammation in the gastrointestinal tract were used to evaluate their anti-inflammatory and modulatory properties on the intestinal microbiota via the signaling pathways involved by oral administration of F. velutipes (FVE) and A. polytricha (APE). Mice were daily received 3%DSS in the drinking water followed by the daily administration of FVE and APE. The food consumption, weight variation and DAI score were assessed during the experiment and inflammatory parameters, mRNA and protein expressions to determine the possible signaling pathways involved, and the gut microbiota from the cecum by high-throughput sequencing. Data showed that APE and FVE improved clinical symptoms, inflammatory cytokines and oxidative markers. They also attenuated the mRNA and proteins expressions in colon tissue. Moreover, APE and FVE regulated DSS-induced intestinal dysbiosis and stimulated the SCFAs production. Overall, APE and FVE could improve DSS-induced IBD in mice suggesting that they represent novels therapeutic drugs and could be used as prebiotic to modulate the gut microbiota and preserve intestinal integrity. Highlights: The main bioactive molecules were collected from A. polytricha and F. velutipes. APE and FVE attenuated clinical factors and regulated inflammatory cytokines. APE and FVE inhibited NF-κB and MAPK/ERK as well as stimulated Keap1/nrf2 signaling pathways. APE and FVE modulated the gut microbiota via increasing SCFAs contents.